A Personalized Approach to the Treatment of Patients with Latent Stage Angle-Closure Glaucoma - E. I. Belikova; G. A. Sharova (Oftalʹmologiâ, 2020)
A latent stage of angle-closure glaucoma is a functional unit, which leads to the progression of glaucoma in the absence of treatment.Purpose. To determine tactics and to evaluate the results of a personalized approach to treatment in patients with a latent stage of angle-closure glaucoma. Patients and methods. An analysis of surgical treatment of 35 patients (56 eyes) with latent stage of  angleclosure glaucoma has been carried out. The first group (I) included patients with accommodative a  transparent lens, the absence or the presence of ametropia is not more than 1.0 diopter, a high rating for the quality of life according to the questionnaire VF14 (Visual Function). All patients in group I were treated with a personalized combined laser iridectomy with a preliminary coagulation of the iris. The second group (II) included patients with a little accommodative, transparent or opaque lens, the absence or presence of  ametropia more than 1.0 D, a low ranking for the quality of life. The second group of patients was divided into  two subgroups: IIA — all the patients underwent personalized combined laser iridectomy with a preliminary coagulation of the iris; IIB — all the patients underwent phacoemulsification with intraocular lens implantation. The result of surgical treatment was evaluated in terms of the depth of the anterior chamber, the degree of  opening of the anterior chamber angle in accordance with the classification of van-Beuningen, according to the questionnaire of quality of life VF14. Results. The degree of opening of the eye anterior chamber angle and anterior chamber depth have been increased in all the groups, but the indicators have varied. In group IIB the results were significantly effective and credible. In group I, the ranking of quality of life after laser iridectomy was not changed, remained consistently high; in the IIB it was significantly increased, while in the IIA it remained low. Conclusion. Personalized combined laser iridectomy with a preliminary coagulation of the iris and phacoemulsification with IOL implantation are effective methods of treatment the latent stage of angle-closure  glaucoma. The laser iridectomy as a treatment of latent stage of angle-closure glaucoma is sufficient in the case of conserved accommodation, of the crystalline lens, the absence of ametropia and the high rating for the quality of life questionnaire VF14. Phacoemulsification with intraocular lens implantation is required in the case of ametropia, poor accommodation or its absence and especially cataract changes in the lens, the low for the quality of life.